2008
DOI: 10.1128/aem.01288-08
|View full text |Cite
|
Sign up to set email alerts
|

BioluminescentAspergillus fumigatus, a New Tool for Drug Efficiency Testing and In Vivo Monitoring of Invasive Aspergillosis

Abstract: Aspergillus fumigatus is the main cause of invasive aspergillosis in immunocompromised patients, and only a limited number of drugs for treatment are available. A screening method for new antifungal compounds is urgently required, preferably an approach suitable for in vitro and in vivo studies. Bioluminescence imaging is a powerful tool to study the temporal and spatial resolutions of the infection and the effectiveness of antifungal drugs. Here, we describe the construction of a bioluminescent A. fumigatus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 41 publications
5
118
0
Order By: Relevance
“…To obtain oils and extracts active against C. krusei and A. fumigatus is important because C. krusei has been recognized as a potentially multidrug-resistant pathogen and A. fumigatus is the main cause of invasive aspergillosis in immunocompromised patients; moreover, only a limited number of drugs are available (Brock et al, 2008, Pfaller et al, 2008. Additionally, both C. krusei and A. fumigatus, have the ability to form biofilms in biomedical devices that come in contact with skin, mucosal or inert surfaces (Quindós et al, 2009;Seidler et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain oils and extracts active against C. krusei and A. fumigatus is important because C. krusei has been recognized as a potentially multidrug-resistant pathogen and A. fumigatus is the main cause of invasive aspergillosis in immunocompromised patients; moreover, only a limited number of drugs are available (Brock et al, 2008, Pfaller et al, 2008. Additionally, both C. krusei and A. fumigatus, have the ability to form biofilms in biomedical devices that come in contact with skin, mucosal or inert surfaces (Quindós et al, 2009;Seidler et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is important because C. krusei has been recognised as a potential multidrug-resistant pathogen due to its intrinsic fluconazole resistance and recent reports showing a decreased susceptibility of the pathogen to both flucytosine and amphotericine B (Pfaller et al 2008). Aspergillus fumi-gatus is the main cause of invasive aspergillosis in immunocompromised patients and only a limited number of drugs are available for treatment (Brock et al 2008). In addition, recent studies have reported emergence of azole resistance in this species (Snelders et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A. fumigatus strain C3. The bioluminescent A. fumigatus strain C3 was cultured on malt extract agar slants as described earlier 10 and bioluminescence of the strain was confirmed in vitro by determination of light emission from cultures grown for 8 h in RPMI medium by using an IVIS 100 system (Xenogen Corporation).…”
Section: Methodsmentioning
confidence: 99%
“…10 In vivo bioluminescence imaging allowed studying the progression of infection in individual animals. Significant differences in the temporal and spatial manifestation of organ infections were observed in dependence of the immune status of infected animals.…”
Section: Do Not Distributementioning
confidence: 99%